(untitled) (Revista Contexto & Educação, 2024)
This work aims to present some foundations that point to the possibility of crossing the concepts of narrative imagination and aesthetic training as an implement of teaching training and performance in Higher Education, in search of an integral and more humane training. This article seeks to satisfactorily answer the following question: is it possible to approximate the concepts of narrative imagination and aesthetic training as an implement of teaching training and performance in Higher Education? It is, therefore, a basic research, with a qualitative approach, based on a bibliographic procedure, with hermeneutic-analytical and reflective analysis of the theoretical concepts presented, in order to combine new understandings about the discussions presented. With the completion of the research, it is possible to conceive that thinking about teacher training in Higher Education, in order to approach and internalize in practice the concepts of sensitive, aesthetic and narrative imagination training, can contribute to the exercise of student training. more effectively, in order to make this education more inclusive, of belonging and acceptance of the other.